Analysis and design of injection-locking steerable active array applicator - Thongsopa, Chanchai; Krairiksh, Monai; Mearnchu, Anat; Srimoon, Duang Arthit (My University, 2002)
In this paper, the analysis, design and experimental results of active array applicator are presented. The injection-locking technique is used to alter the magnitude of the microwave sources so that the steering of near fields can be achieved. This technique can be applied for microwave hyperthermia cancer treatment to provide the large uniform temperature distribution. The complexity of the system can be reduced by using this technique. The study shows that the temperature distribution can be controlled by varying the modulation index, modulating frequency and initial phase of modulating signal. The temperature distribution is also affected by applicator configuration, spacing between applicators, and heating time. The Spectral Domain approach is used to analyze the near field and then the near field data are used to find the temperature distribution by using the Finite Difference method. The study is carried out at frequency of 2,450 MHz. This design is useful for implementation of the low cost steerable applicator.
Keywords: Active slot applicator; Injection-locking technique; Non-invasive applicator; Steerable applicator